WORD RECOGNITION OR SOCIAL BEHAVIOUR?: LITERACY ISSUES IN SECOND OR FOREIGN LANGUAGE READERS OF ENGLISH IN DEVELOPING COUNTRIES - Mick Randall (Universitas Katolik Indonesia Atma Jaya, 2008)
This paper critically examines the four resources model of literacy (Freebody & Luke, 1999) in the context of the ESL/EFL reader in a poorly resourced public education system such as exists in many parts of the developing world. It critically examines the impact that issues such as globalization may have on the learning and teaching of English literacy. It argues that the special literacies that are often portrayed as essential in the so-called changed socio-political climate are, in fact, only relevant at best to certain social and economic groups in society and at worst to certain types of developed society. It argues that aspects of the four resources model and critical literacy in general are important aspects to take into account in literacy programmes, but they will impact differently at different stages of literacy and in different social and economic circumstances. The paper suggests that more attention needs to be paid to basic word recognition skills in second language readers and will review recent research done in Malaysia and Singapore with Bahasa Malayu speakers and Chinese which suggests that word recognition procedures in ESL readers of English may be radically different, that these differences should be taken into account when designing decoding programmes and thus when designing initial literacy programmes. Keywords: Globalization; Special literacies; Critical literacies; Literacy programmes; Word recognition.